Răspuns :
Explicație pas cu pas:
2.
[tex]3\{3(2x + 3) - 3\left[5(7 - 4x) + 18(x - 2)\right] - 5\} = 5\left[33 - 8(x + 7) \right] - 16 \\ [/tex]
[tex]3[6x + 9 - 3(35 - 20x + 18x - 36) - 5] = 5(33 - 8x - 56) - 16 \\ [/tex]
[tex]3[6x + 9 - 3(- 2x - 1) - 5] = 5(- 8x - 23) - 16 \\[/tex]
[tex]3(6x + 9 + 6x + 3 - 5) = - 40x - 115 - 16 \\ [/tex]
[tex]3(12x + 7) = - 40x - 131 \\[/tex]
[tex]36x + 21 = - 40x - 131 \\[/tex]
[tex]36x + 40x = - 131 - 21\\[/tex]
[tex]76x = - 152 = > x = - 2[/tex]
3.
[tex]\frac{2x + 9}{3} - \frac{5(2x + 11)}{6} + 4 \frac{1}{2} = 1 \frac{1}{3} - \frac{3x + 8}{2} \\ [/tex]
[tex]\frac{2(2x + 9)}{6} - \frac{5(2x + 11)}{6} + \frac{9}{2} = \frac{4}{3} - \frac{3(3x + 8)}{6} \\ [/tex]
[tex]\frac{4x + 18}{6} - \frac{10x + 55)}{6} + \frac{3 \times 9}{6} = \frac{2 \times 4}{6} - \frac{9x + 24)}{6} \\ [/tex]
[tex]4x + 18 - 10x - 55 + 27 = 8 - 9x - 24\\ [/tex]
[tex]- 6x - 10 = - 9x - 16\\ [/tex]
[tex] - 6x + 9x = - 16 + 10[/tex]
[tex]3x = - 6 = > x = - 2[/tex]